(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
In this study we investigated the effect of saline solution in different concentration (0.1–1.0 mM NaCl) on the development of conidial inoculum of powdery mildew pathogen Blumeria graminis (DC) Speer. on soft wheat Triticum aestivum L. Dynamics of development and of differentiation of infesting structures of the powdery mildew was investigated using scanning electronic microscopes. After the salt solutions were added, the conidial germination of powdery mildew fungi was slow, but germ tubes were formed, appressoria were not formed. It is assumed that the action of various unfavorable factors is based on a common mechanism associated with an increase in the level of active oxygen forms in plant tissues.